On the approximation of functions from Weyl-Nagy classes by Zygmund sums in the $L_q$ metric - Kostich, M. V.; Костич, М. В. (Institute of Mathematics, NAS of Ukraine, 1999)
In the integral metric, estimates exact by order are found for deviations of the Zygmund linear means from functions, which belong to Weyl-Nagy classes.